2020
DOI: 10.1136/tobaccocontrol-2020-055956
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to messages about smoking, vaping and COVID-19: two national experiments

Abstract: IntroductionThe pace and scale of the COVID-19 pandemic, coupled with ongoing efforts by health agencies to communicate harms, have created a pressing need for data to inform messaging about smoking, vaping, and COVID-19. We examined reactions to COVID-19 and traditional health harms messages discouraging smoking and vaping.MethodsParticipants were a national convenience sample of 810 US adults recruited online in May 2020. All participated in a smoking message experiment and a vaping message experiment, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 54 publications
(61 reference statements)
4
42
0
Order By: Relevance
“…The fact that including COVID-19-related warnings on cigarette packets did not substantially increase negative affective ratings across all smokers, is consistent with other recent findings that smokers reported equal emotional ratings (ie, fear, anxiety, sadness) of social media messages that contained THWs versus those that also contained C19HWs. [14] Therefore, despite the recent evidence that COVID-19 has prompted an increase in the motivation to quit, [12] the current evidence suggests that C19HWs may not be more effective than THWs in eliciting a negative affective response, and subsequent cessation, when ignoring the influence of impulsivity on participants' responses.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The fact that including COVID-19-related warnings on cigarette packets did not substantially increase negative affective ratings across all smokers, is consistent with other recent findings that smokers reported equal emotional ratings (ie, fear, anxiety, sadness) of social media messages that contained THWs versus those that also contained C19HWs. [14] Therefore, despite the recent evidence that COVID-19 has prompted an increase in the motivation to quit, [12] the current evidence suggests that C19HWs may not be more effective than THWs in eliciting a negative affective response, and subsequent cessation, when ignoring the influence of impulsivity on participants' responses.…”
Section: Discussionmentioning
confidence: 59%
“…Currently, only one study has explored reactions to health messages highlighting the elevated COVID-19 severity for smokers. [14] In this study, participants viewed traditional health warnings (THW) and COVID-19-related health warnings (C19HW) as social media posts. Based on self-reported perceived effectiveness, negative emotion, and perceived harm, the authors report that C19HW messages were no more or less effective than THW messages.…”
mentioning
confidence: 99%
“…In line with our findings related to perceived risk of COVID-19 and attempts to quit, prior work by Grummon et al using a convenience sample of U.S. adults found that both messaging related to traditional harms of smoking and those specifically related to COVID-19 had higher perceived effectiveness for discouraging smoking compared to control messages. 21 In contrast, while messaging about traditional harms of vaping were associated with higher perceived effectiveness for discouraging vaping compared to control, the same was not seen for COVID-19 related messages. 21 Thus, education of smokers on the relationship between smoking and COVID-19 risk may serve as an important motivator for cessation and/or reducing potential increases in product use.…”
Section: Discussionmentioning
confidence: 92%
“…21 In contrast, while messaging about traditional harms of vaping were associated with higher perceived effectiveness for discouraging vaping compared to control, the same was not seen for COVID-19 related messages. 21 Thus, education of smokers on the relationship between smoking and COVID-19 risk may serve as an important motivator for cessation and/or reducing potential increases in product use. Further research is necessary to assess the effects of public health messaging on smoking and vaping during the pandemic and optimize messaging content for these individuals.…”
Section: Discussionmentioning
confidence: 92%
“…Future work is now required to determine whether the higher motivation to quit smoking in some smokers persists beyond the peak of the pandemic and is transferred into lasting change in actual smoking behaviour, as motivation alone is not enough to result in long-lasting cessation (Borland et al, 2010). It may be that interventions can be utilised to enhance any increase in motivation to quit in response to the novel harm posed by COVID-19, though this will be dependent upon the progression of the virus globally (Grummon et al, 2020). It should be noted that the findings may be limited to a UK based sample, as the international response to COVID-19 has varied (Hale et al, 2020), meaning that replication is other samples is required.…”
Section: Discussionmentioning
confidence: 99%